PENGEMBANGAN MODUL AJAR BERBASIS MULTIMEDIA PADA MATA KULIAH STATISTIKA PENDIDIKAN - Andoko Ageng Setyawan; Putri Wahyuni (Universitas Sultan Ageng Tirtayasa, 2019)
This type of research is development research using the initial two-stage analysis and formative final analysis. The first stage of this research is called the Stage of Early Preliminary Analysis (front-end analysis) which aims to determine the mathematics learning goals that must be approved by students. This activity is followed by the distribution of mathematical learning compiled based on aspects of the use of computers as multimedia. Through justification, analysis and evaluation of competent mathematical education experts, the initial mathematical learning model was developed. The data for the research that I obtained was obtained from various studies, such as field observations, documentation and interviews. Analysis of the content of competencies in the curriculum and adapted to data on regulations, materials that can be made in learning mathematics in the field are important aspects in developing teaching materials. Furthermore, as a Formative Analysis Phase that aims to validate, analyze, test, develop, analyze, and revise the initial concept. This will be tested on several students as a sample to see more about the readability of the material that has been designed. Data for this device was obtained from questionnaires and interviews. This stage will produce a model of testing mathematics learning in the form of multimedia computer-based teaching materials. Based on the results of the study, it can be concluded that the overall validity of the validator 81.14 means included in the very valid category. Based on the table of trial calculations, obtained a very practical category with an overall result of 86.93%. This means that the learning media developed is very easy to use by students in the learning process. Keywords: Multimedia Learning, Development of Teaching Modules